The readiness of China towards an economic phenomenon: A hedge fund industry perspective - Wang, Junyi (2007)
China is considered the most promising emerging economies that greatly benefit from globalization. This is eminent from foreign direct investments that the country receives attracted by the enormous demand, cheap labor and sizeable business opportunities. However, it is argued that economic growth and the success of political transition will be hampered if financial markets are immature, especially Hedge Fund industry. To this consideration, authorities and institutions took an extra mile apart from accelerating liberalization efforts. This study found that the financial system of China and the level of its integration to global markets are observable to the hedge fund development not only in China but the Greater China which includes Hong Kong and Taiwan. Second, it is also found that hedge fund in the Mainland China is underdeveloped largely attributed to limited development of financial institutions. Third, the source of promising trade and financial liberalization of Mainland in the future, political direction and leadership serves as the most influential factor in shaping the hedge fund sector in the country.